IMMUNOMODULATORY EFFECTS OF HUMAN ALLOGENEIC MESENCHYMAL STEM CELLS IN AGING-RELATED FRAILTY: A SYSTEMATIC REVIEW AND META-ANALYSIS OF RANDOMIZED CONTROLLED TRIALS - Wedharga, I Gede Putu Adhi; Jaya, Ferdinand Wiliam (JURNAL WIDYA MEDIKA, 2026)
Aging-related frailty is associated with immune dysregulation, including chronic inflammation and immunosenescence. Human allogeneic mesenchymal stem cells (hMSCs) have been proposed as immunomodulatory therapies; however, the responsive immune domains remain unclear. This systematic review and meta-analysis explored immune and inflammatory biomarkers reported in randomized controlled trials (RCTs) of hMSC therapy for aging-related frailty. Major databases were searched through April 2026 for RCTs enrolling adults aged ≥60 years with clinically diagnosed frailty. Outcomes encompassed innate inflammation, adaptive immune activation and composition, immunosenescence-related measures, and alloimmune responses. Biomarkers reported by at least two trials were pooled using a random-effects model. Three RCTs (n = 196) met the eligibility criteria. hMSC therapy was associated with a significant reduction in tumor necrosis factor-α (TNF-α) at 6 months (mean difference [MD] −0.61, 95% CI −1.08 to −0.14), while interleukin (IL)-6, IL-8, interferon (IFN)-γ, and the CD4/CD8 ratio showed no consistent effects. Limited alloimmune data indicated no clinically meaningful immune sensitization. Overall, hMSC therapy may preferentially attenuate innate TNF-α–driven inflammation, while other immune effects remain exploratory.